Comparative Investigation on the Crystal Structures, Hirshfeld Surface Analysis, Antitubercular Assays, and Molecular Docking of Regioisomeric 1, 2, 3‐Triazoles. Issue 15 (20th April 2022) - Anand, Ashish; Sindogi, Kishorkumar; Dixit, Sheshagiri R.; Shetty, Richa P.; Pujar, Gurubasavaraj V.; Kulkarni, Manohar V.; Guru Row, Tayur N.
Abstract: 1, 2, 3‐triazole system is readily obtained by the click reaction in a facile and regioselective way. Regioselectivity is introduced under Copper(CuAAC), and Ruthenium(RuAAC) catalysed azide‐alkyne cycloaddition reaction furnishing 1, 4 and 1, 5‐disubstituted triazoles, respectively. These two regioisomeric systems offer discrete physicochemical and medicinal properties based on crucial binding interactions and biocompatibility with the biological targets. In this regard, a comparative investigation on the coumarin‐linked regioisomeric 1, 2, 3‐triazoles via its crystal structure, Hirshfeld surface analysis, and antitubercular assays and molecular docking are reported. It sheds light on the variation of in vitro antitubercular efficacy against Mycobacterium tuberculosis H37 Rv followed by molecular docking studies that justify the prominent interactions at the binding site. Further, solid‐state and Hirshfeld surface analysis provided significant crystallographic insights on the critical intermolecular interactions that dictate the crystal packing in these systems. Thus structure‐property correlation for these regioisomeric systems can open new avenues in drug design and discovery. Abstract : A comparative analysis on the regioisomeric 1, 2, 3‐triazole systems obtained via Click chemistry is explored. Solid‐state interactions coupled with in vitro anti‐tubercular assays and molecular docking shed light on the contrasting yet inherent behaviour of regioisomeric 1, 2, 3‐triazoles. 1, 5‐regioisomer showed better efficacy against anti‐tubercular assays and solid‐state profiling via single crystal X‐ray and Hirshfeld analysis further revealed the subtle differences in view of the substitution and regioisomerism, that can appreciably modify the solid‐state packing and hence properties.